Residential Counselors and Self Care: A Retrospective Qualitative Study of Archival Interview Data - Rebekah Lemmons Ph.D; Steve Zanskas Ph.D (SAGE Publishing, 2019)
Objectives: The purpose of this qualitative inquiry was to understand the barriers related to effective self-care for master's level residential counselors. Methods: Archival interview transcripts of 77 residential counselors were analyzed utilizing a social constructivist lens to identify perceived barriers to effective self-care. Themes related to levels of self-care influences including individual, supervisory, and organizational barriers to effective self-care emerged. Results: Results reflected those themes specifically by indicating that counselors can take steps to actively engage in wellness pursuits to promote self-care. Similarly, supervisors and organizations can enhance or impede a counselor's ability to engage in self-care. Conclusions: Counselors should select work settings that have both supervisory and organizational supports for self-care. This includes encouraging a culture of wellness through support, development, coverage for time off, and other related areas. Implications show that practices and policies are needed to promote effective self-care across individual, supervisory, and agency domains.